2018
DOI: 10.2174/1381612823666170714150118
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNA in Lung Cancer-Potential Biomarkers and Therapies

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs, which downregulate gene expression by repressing or degrading mRNA targets. Lung cancer (LC), together with liver and colorectal cancers are the three leading causes of cancer death worldwide, and 80% of LCs belong to non-small cell lung cancers (NSCLCs). Despite a great advancement in developing distinct and delicate tools for early diagnosis and targeted therapies over the last decade, only about 15% of the NSCLC patients eventually survived. MiRNAs are frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 144 publications
0
41
0
Order By: Relevance
“…Therefore, it is of great significance to find the factors related to the occurrence, development and metastasis of lung cancer in order to predict its survival and prognosis and provide possible means for treatment. For a long time, the research on lung cancer has mostly focused on the cancer cells themselves, mainly due to changes in gene level [ [18] , [19] 20 ]. In contrast, there is little discussion about the chronic infection of pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to find the factors related to the occurrence, development and metastasis of lung cancer in order to predict its survival and prognosis and provide possible means for treatment. For a long time, the research on lung cancer has mostly focused on the cancer cells themselves, mainly due to changes in gene level [ [18] , [19] 20 ]. In contrast, there is little discussion about the chronic infection of pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that miR-148a inhibits the migratory and invasive potential of cells through targeting and regulating Wnt1 expression (16). Moreover, miRNAs can also serve as early diagnostic molecular markers in LC, as well as therapeutic targets and treatment evaluation markers (6,17). miR-30a expression in plasma is significantly elevated in patients with early LC, so its detection may be a new non-invasive method for early screening and differential diagnosis of patients with NSCLC (18).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA expression signature for lung cancer was characterized by previous studies (27,28). Recently, a number of individual studies reported the dysregulated miRNAs in NSCLC and the functional roles of the individual miRNAs were investigated (2935).…”
Section: Discussionmentioning
confidence: 99%